A Longitudinal Examination of the Associations Between Shyness, Drinking Motives, Alcohol Use, and Alcohol‐Related Problems. (24th July 2015) - Young, Chelsie M.; DiBello, Angelo M.; Traylor, Zachary K.; Zvolensky, Michael J.; Neighbors, Clayton
<x xml:space="preserve">Abstract</x> Background The current study evaluated the roles of drinking motives and shyness in predicting problem alcohol use over 2 years. Methods First‐year college student drinkers (n = 818) completed assessments of alcohol use and related problems, shyness, and drinking motives every 6 months over a 2‐year period. Results Generalized linear mixed models indicated that shyness was associated with less drinking, but more alcohol‐related problems. Further, shyness was associated with coping, conformity, and enhancement drinking motives, but was not associated with social drinking motives. However, when examining coping motives, moderation analyses revealed that social drinking motives were more strongly associated with coping motives among individuals higher in shyness. In addition, coping, conformity, and enhancement motives, but not social motives, mediated associations between shyness and alcohol‐related problems over time. Finally, coping motives mediated the association between the interaction of shyness and social motives and alcohol‐related problems. Conclusions Together, the results suggest that shy individuals may drink to reduce negative affect, increase positive affect, and fit in with others in social situations, which may then contribute to greater risk for subsequent alcohol‐related problems.